Analisis Perencanaan Laba Melalui Cost Volume Profit (Cvp): Studi Kasus UMKM Ayam Potong Deni Jaya - Azzahra Oktaviani, Tia; Suherman, Enjang (Jurnal Etnik: Ekonomi-Teknik, 2024)
This study aims to understand effective planning in terms of sales and expenses to generate profit at UMKM Deni Jaya. To achieve optimal profit, business operators need to implement Cost Volume Profit (CVP) analysis. During its operation, UMKM Deni Jaya's broiler chicken business has never conducted CVP analysis, resulting in suboptimal profits. This research focuses on CVP analysis in the broiler chicken business of Deni Jaya. The method used is quantitative descriptive with a case study approach, where researchers collect financial data directly from UMKM Deni Jaya and analyze it. CVP analysis includes Break-Even Point, Contribution Margin, Margin of Safety, Degree of Operating Leverage, and profit planning. The research results for UMKM Deni Jaya show that in 2024, the BEP (units) requires selling 5,470 kg, and the BEP (Rupiah) needs to achieve revenue of Rp 19,450,000 to avoid losses. The Contribution Margin ratio is 26%, the maximum allowable Margin of Safety decrease is 81%, the Degree of Operating Leverage indicates a Contribution Margin 1.23 times the operating profit, and UMKM Deni Jaya's profit planning aims for a 10% profit increase, reaching a profit of Rp 273,930,000.